Cardiac Rehabilitation Knowledge and Attitudes of Cardiology Fellows. Issue 1 (January 2021) - Kellar, Garrett; Hickey, Gavin W.; Goss, Fredric; Fertman, Carl; Forman, Daniel E.
Abstract : Purpose: Cardiac rehabilitation (CR) is underutilized with only 8-31% of eligible patients participating. Lack of referral and lack of physician endorsement are well-known barriers to participation. Physicians who lack insights regarding CR are less likely to refer patients and recommend it. Cardiology fellows are early career physicians who spend a significant amount of time treating patients eligible for CR. At one institution's cardiology fellowship program, we sought to assess fellow attitudes and knowledge base regarding CR and to determine their facilitators and barriers to CR endorsement and referral. Methods: University of Pittsburgh Department of Medicine Cardiology fellows were surveyed and interviewed to assess CR knowledge, attitudes, and perceived facilitators and barriers to CR endorsement and referral. Results: The cardiology fellows at this institution had strong belief in the benefits and cost-effectiveness of CR. Despite their support of CR, they had low CR knowledge scores. Perceived impediments to CR included complicated logistics of CR operations, limited communication between CR staff and fellows, limited time with patients, presumed patient barriers, perceived self-barriers, and poor understanding of referral processes (particularly as they varied in each hospital in which they rotated). Perceived supports to CR included greater awareness of evidence-based outcomes, awareness of patient-centered outcomes, pre-arranged order sets, and reminders for referral. Conclusion: This study revealed perceptions of cardiology fellows at one institution regarding CR that have not been considered previously. Key barriers to endorsement and referral to CR were exposed as well as opportunities to overcome them. Fellowship training affords an important opportunity to improve CR education, and to potentially improve participation of eligible patients for this important aspect of care. Abstract : Supplemental Digital Content is Available in the Text.Cardiology fellows play a key role in the referral and endorsement of cardiac rehabilitation (CR) in teaching hospitals. The present study surveyed and interviewed cardiology fellows at one institution. Results demonstrated they have low knowledge regarding CR, with multiple perceived barriers to endorsement and referral. Fellowship education programming can be targeted to overcome these barriers to CR care.